2023
DOI: 10.3390/v15040902
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Viral Type I Fusion Proteins: Inhibitors of Influenza Virus Hemagglutinin and the Spike Protein of Coronavirus

Abstract: The fusion of viral and cell membranes is one of the basic processes in the life cycles of viruses. A number of enveloped viruses confer fusion of the viral envelope and the cell membrane using surface viral fusion proteins. Their conformational rearrangements lead to the unification of lipid bilayers of cell membranes and viral envelopes and the formation of fusion pores through which the viral genome enters the cytoplasm of the cell. A deep understanding of all the stages of conformational transitions preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Recent findings have shed light on the varying antiviral efficacy of disinfectants. Although some chemicals demonstrate high effectiveness by strongly denaturing or disrupting the target surface proteins, others exhibit moderate effectiveness, which may be attributed to their lower binding affinities or less precise targeting of the complex and variable structures of viral proteins [ 16 , 17 ]. The chemical disinfectants studied could potentially exhibit diverse modes of action against viral surface proteins, including direct (i.e., protein denaturation and membrane disruption by phytochemicals, aldehydes, and alcohol-base disinfectants), indirect (i.e., oxidative damage by hydrogen peroxide and chlorine), and multi-faceted (i.e., both oxidative damage and direct binding interactions by peracetic acid and ozone).…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings have shed light on the varying antiviral efficacy of disinfectants. Although some chemicals demonstrate high effectiveness by strongly denaturing or disrupting the target surface proteins, others exhibit moderate effectiveness, which may be attributed to their lower binding affinities or less precise targeting of the complex and variable structures of viral proteins [ 16 , 17 ]. The chemical disinfectants studied could potentially exhibit diverse modes of action against viral surface proteins, including direct (i.e., protein denaturation and membrane disruption by phytochemicals, aldehydes, and alcohol-base disinfectants), indirect (i.e., oxidative damage by hydrogen peroxide and chlorine), and multi-faceted (i.e., both oxidative damage and direct binding interactions by peracetic acid and ozone).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4C key protein-ligand interactions that define this site using Wuhan strain numbering include S2 residues that are just C-terminal of the fusion peptide (F823, L826, and F833) and residues (P1057, H1058) from the S2 connector domain (CD) (res: 986-1035). The borneol ester derivative binding site on the SARS-CoV-2 Spike is supported by sequence analysis, extensive molecular docking, and molecular dynamic (MD) simulations and supported by the rationale of how camphecene derivatives are proposed to bind to influenza HA [81][82][83].…”
Section: Other Proposed Fusion Inhibitor Binding Sites On the S2 Segmentmentioning
confidence: 88%
“…In summary, toremifene, nelfinavir, and a variety of natural product saponin derivatives are proposed to bind at Site 4, and presumably, small-molecule binding at this site acts to stabilize the prefusion conformation. Moving our attention to another proposed binding site, as shown in Figure 4, Site 6 on the S2 segment of the SARS-CoV-2 Spike is analogous to the proposed camphecene binding site on Influenza HA [81], which was confirmed by mutagenesis and resistance Moving our attention to another proposed binding site, as shown in Figure 4, Site 6 on the S2 segment of the SARS-CoV-2 Spike is analogous to the proposed camphecene binding site on Influenza HA [81], which was confirmed by mutagenesis and resistance mutations [82,83]. For a novel series of borneol ester derivatives, Yarovaya et al identified that derivatives 11 and 21 had the greatest activity in pseudovirus infections in both original Wuhan and Delta (B.1.617.2) strains [84].…”
Section: Other Proposed Fusion Inhibitor Binding Sites On the S2 Segmentmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent findings have shed light on the varying antiviral efficacy of disinfectants. Although some chemicals demonstrate high effectiveness by strongly denaturing or disrupting target surface proteins, others exhibit moderate effectiveness, which may be attributed to their lower binding affinities or less precise targeting of the complex and variable structures of viral proteins [16,17]. The promising efficacies of some chemicals (i.e., rutin, remdesivir, hexachlorophene, chlorhexidine gluconate, amylmetacresol, and 2-dodecylbenzenesulfonic acid) against specific surface proteins (i.e., glycoprotein gB, glycoprotein gp21, VP8, and hemagglutinin HA) are promising avenues for targeted remediation and therapeutic intervention.…”
Section: Figurementioning
confidence: 99%